Prevalence, mortality and healthcare utilization among Medicare beneficiaries with Hepatitis C in Haemodialysis units. Issue 11 (2nd August 2019) - Deshpande, Rati; Stepanova, Maria; Golabi, Pegah; Brown, Kimberly; Younossi, Zobair M.
Abstract: Hepatitis C (HCV) is more common among patients with end‐stage renal disease requiring haemodialysis compared to the general population. Thus, we aimed to assess trends in prevalence, health resource utilization and mortality among Medicare beneficiaries with HCV on haemodialysis. This is a retrospective study of outpatient and inpatient claims for Medicare beneficiaries receiving haemodialysis (2005‐2016). A total of 291 663 subjects on haemodialysis were included (67.3 ± 15.2 years, 55% male, 55% white, 49% age‐based eligibility). The prevalence of HCV in subjects on haemodialysis was stable and was significantly higher (mean 4.2% in 2005‐2016, P  = 0.50 for the trend) than in subjects not on haemodialysis (<1%). In multivariate analysis, liver cirrhosis (odds ratio = 3.4 (95% CI = 3.3‐3.6)) was an independent predictor of 1‐year mortality among haemodialysis patients. Mean total inpatient payments in dialysis patients with HCV remained stable during 2005 ($73 803) through 2016 ($72 133) (trend P  = 0.54) while mean total outpatient payment decreased from 2005 ($53 497) to 2016 ($35 439; trend P  = 0.0013). In multivariate analysis, after adjustment for age, gender, race and location, both HCV and cirrhosis remained significant contributors to greater spending [HCV: inpatient +22.1% (+19.2%‐25%), HCV: outpatient +18.4% (+14.6%‐22.2%), cirrhosis: inpatient +59.7% (+56.9%‐62.6%), cirrhosis: outpatient +9.4% (+6.2%‐12.6%)]. In conclusion, HCV‐infected Medicare patients receiving haemodialysis incur greater resource utilization; mortality is higher in patients with cirrhosis only. Although HCV prevalence in Medicare haemodialysis recipients is higher than in patients without haemodialysis, these rates are lower than reported, suggesting potential under‐screening for HCV in this high‐risk population.